RTHP-04. PEDIATRIC STEREOTACTIC RADIOSURGERY FOR BENIGN NEUROLOGIC DISEASE: A 25-YEAR INSTITUTIONAL EXPERIENCE. (11th November 2019) - Sherry, Alexander; Bingham, Brian; Kim, Ellen; Facer, Benjin; Chukwuma, Valentine; Luo, Guozhen; Attia, Albert; Vogel, Jennifer; Cmelak, Anthony
Abstract: Long-term outcomes and sequalae of pediatric stereotactic radiosurgery (SRS) for benign neurologic disease are poorly understood. We sought to explore the efficacy and late effects of SRS in pediatric patients treated our institution. After institutional review board approval, we performed a retrospective analysis of patients age 21 or younger treated between 1990 and 2016. Covariates were summarized with descriptive statistics. 56 consecutive patients were enrolled. Patients were primarily Caucasian (n=51, 93%) males (n=30, 54%). Diagnoses included arterio-venous malformation (n=41, 73%) and functional pituitary adenoma (n=9, 16%) as well as vestibular schwannoma, craniopharyngioma, meningioma, papilloma, and ganglioglioma. Average age was 14 years (95% CI 13–16 years). SRS was often the first intervention (n=22, 44%); treatments prior to SRS included embolization (n=18, 36%) and surgery (n=10, 20%). SRS was typically single fraction (n=45, 94%) with a median total dose of 16 Gy (IQR 15–18 Gy). Most patients had no acute side effects of SRS (n=40, 87%). Median follow-up time after SRS was 12 years (IQR 6–18 years, max 26 years). 91% of patients had no late sequelae of SRS. One patient was diagnosed with radionecrosis one year after repeat SRS for residual malformation. Two patients had malformation hemorrhage. One patient with brainstem malformation developed focal weakness after ischemia from treatment effect; another patient with malformation developed seizures related to SRS edema. Over 673 patient-years following SRS, no patient developed radiation-induced malignancy or malignant transformation. Median disease-free survival after SRS was 6 years (IQR 3–13) with 66% overall local control; 84% of local failures occurred within 5 years of SRS. At last follow-up, 95% of patients remained without evidence of disease with 100% overall survival. These data support the long-term safety and efficacy of pediatric SRS.